A comparative study on refractive index profile based optical fiber designs. (2023) - Roy, Nikita; DasMahapatra, Suddhendu; Tiwari, Manish
Abstract: Fiber optic communication channel has fulfilled the demand for high-speed communication medium. The entire telecommunication industry transformed with optical fiber. Optical fiber finds substantial application within data communication networks too. The optical fiber cable has enabled telecommunications links to be made at larger distances and with very smaller losses within the medium. It also supports a very high data rate. Therefore, due to such prominent benefits, fiber optic communication systems are comprehensively deployed for several major telecommunication applications such as Ethernet systems, Broadband distribution and general computer/data networks. The data rate, the distance of communication, losses, etc. are dependent on the design parameters of optical fiber. The present work reports a comparative analysis of numerous key parameters, such as dispersion, group delay, bending loss, etc. for various refractive index profiles of optical fiber. Through an extensive literature survey, a few realistic refractive index profile-based designs are implemented and compared concerning their parameters.